Aplikasi Pariwisata Kota Malang Berbasis Web Menggunakan Metode User Centered Design - Muhammad Efrizal Febriyan; Ade Davy Wiranata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The City of Malang is one of the favorite destinations in Indonesia which has uniqueness in culture and diverse tourism. Information about tourism has not been handled properly by the government in Malang City. The various tourist attractions in Malang City are not fully known by the public. Therefore, here the author will design a WEB-based Malang City Tourism Application. In designing pages on this website, we will use Visual Studio Code (VS Code) Programming assistance. To get a dynamic website design the author uses PHP and CSS in its creation. In managing all existing databases the author uses the MySQL Database. The results of this research study can provide results in which there is complete information about tourist attractions and accommodations in tourism in Malang City. With the User Centered Design (UCD) method, the interface on the website will be focused on user needs. Furthermore, the result of this design is the creation of an interface that contains various menus, including the login menu, main page menu, package menu, hotel menu, and contact menu. The results of the analysis will involve a sample of 100 respondents.